Changes in cellular immunity and levels of serum cytokins in patients with allergic rhinitis who were treated with topical intranasal steroids - Karlidag, T.; Godekmerdan, A.; Kaygusuz, I.; Keles, E.; Yalcin, S.; Cetiner, H. (Galenos Yayincilik, 2005)
Objectives: Topical intranasal steroids are commonly used in the treatment of allergic rhinitis, because these agents are effective and well-tolerated. The aim of this study was to investigate the changes in serum cytokine levels and in cellular immunity in patients with allergic rhinitis after usage of intranasal steroids. Methods: 22 patients (13 female and 9 male) with allergic rhinitis were included in the study and the ages range from 18 to 49 (mean age 29.6 +/- 10.3). Mometasone furoate (200 mcg/day) was administered intranasal to all patients once a day. The symptoms like sneezing, nasal obstruction, nasal discharge, eye and nose itching and smell disorders were examined in controls and before the treatment. Serum samples were taken from patients before treatment, after one-week treatment and after one-month treatment, and the serum levels of interleukin 1 and 4 (IL-1 and IL-4), interferone-. (INF-gamma), tumor necrosis factor-a (TNF-alpha), total IgE, CD3(+), CD4(+), CD8(+), CD19(+) and CD16(+) + CD56(+) were measured. Results: It was observed that the symptoms decreased partially after one-week and decreased significantly after one-month usage of topical intranasal steroids. When compared to the pretreatment term, the increase in the levels of IFN-. and decrease in the levels of IL-4 and total IgE, and slight increase in the levels of TNF-a were determined. There were no statistically significant differences in the levels of serum cytokines at the pretreatment term and after oneweek treatment. The increase (p<0.05) in the levels of IFN-gamma and the decrease (p<0.001) in the levels of IL-4 and total IgE after onemonth treatment were statistically significant, when compared to the pretreatment term. No changes were observed in the subgroup of serum lymphocytes. Conclusion: Topical nasal steroids, which are commonly used in patients with allergic rhinitis, had effects on serum levels of IFN-gamma and IL-4 but had not cause changes in cellular immunity.
Keywords: Allergic rhinitis; nasal steroid; cytokine; cellular immunity